The Importance of the Trigeminal Cardiac Reflex in Rhinoplasty Surgery. Issue 2 (August 2015) - Özçelik, Derya; Toplu, Gaye; Türkseven, Arzu; Sezen, Gülbin; Ankarali, Handan
<x xml:space="preserve">Abstract</x> Background Trigeminocardiac reflex (TCR) consists of bradycardia or asystole along with hypotension and apnea coinciding with stimulation of the trigeminal nerve. During rhinoplasty procedures, we noticed that local anesthetic solution (LAS) application to the columellar area results in bradycardia. We planned to conduct a randomized prospective study on 47 patients undergoing rhinoplasty to demonstrate the characteristics of TCR arising from the columella. Method Local anesthetic solution containing 2% prilocaine with 1:80, 000 adrenaline was applied under standard general anesthesia protocol. In group 1 (study group, n = 24), 2 mL of LAS was applied to the columella. In group 2 (control group, n = 23), 2 mL of LAS was applied to the nasal dorsum. In group 3 (control group, n = 20), after LAS was applied to nasal dorsum in group 2, we waited for 10 minutes. Then, 2 mL of LAS was applied to the columella. Here, recordings were taken for the columella. Heart rate (HR) and blood pressure (BP) were recorded just before needle insertion (baseline level), at the time of needle insertion (NIT) to the columella or dorsum, and after the 1st, 5th, 10th, 30th, and 60th seconds. Results Transient bradycardia (≥20% drop in HR) was observed in 33% of the patients in group 1. Decrease in HR compared to the baseline level in group 1 was significantly greater than that of groups 2 and 3 at all times (P ⩽ 0.05). Systolic BP in NIT and in 60th second in group 1, only in NIT in group 2 was significantly lower than that of baseline levels (P ⩽ 0.05). Conclusions We concluded that stimulation of a sensory branch of the trigeminal nerve in the columellar area leads to TCR under general anesthesia by eliciting clinical hypotension with a drop in systolic BP and in HR of more than 20% compared to the baseline level. Knowing the existence of a certain TCR area will be helpful to the surgeon and anesthesiologist to exercise extra vigilance and to make continuous and meticulous monitoring of the electrocardiogram, HR, and BP during which the TCR may be precipitated such as local anesthetic infiltration to the columellar area in rhinoseptoplasty operations.